SIGNIFICANCE OF LEFT ATRIAL STRAIN ASSESSMENT OF IN THE PEDIATRIC POPULATION - Begić, Zijo (Medicinski podmladak, 2024)
The clinical outcome of chronic mitral regurgitation (MR) in children and adolescents, specifically the time it takes for MR to develop significant changes in the configuration and function of the left atrium (LA), is a relatively understudied area. There are numerous echocardiographic parameters that demonstrate significant changes in the size, volume, and functional behavior of the LA, but they lack the ability for early and fine detection of LA dysfunction. Left atrial strain (LAS) analysis represents a newer non-invasive technique for assessing LA function and early detection of its deformation and dysfunction. In the analysis of patients with chronic and significant MR, it emerges as a method that could verify early deformative, functional, and possibly fibrotic changes in the LA and thus predispose rhythm disturbances and clinical manifestations. This study related to strain analysis of LA function which can have prognostic and clinical implications in pediatric cardiology and be of great assistance in deciding when to initiate MR treatment.